Tony Angelo and the University of the South Pacific - Farran, Sue (Victoria University of Wellington Law Review, 2008)
The author, having served as a Senior Lecturer and Associate Professor at the University of South Pacific, pays tribute to Professor Tony Angelo’s involvement in that University. The author notes that Professor Angelo was instrumental in the structuring and content of the Bachelor of Laws degree, and has continued to support the University in several different ways. The original aim of its law school, which remains unchanged, is to produce graduates who are appropriately prepared for a wide range of employment and service opportunities within the region and to make an outstanding contribution to the South Pacific communities. Professor Angelo has been, and continues to be, a key player in that mission.